2006
DOI: 10.1021/op060085+
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization in the Presence of a Liquid−Liquid Phase Separation

Abstract: This paper presents and compares crystallization experiments of an active pharmaceutical ingredient and a biological molecule in the presence of a liquid−liquid phase separation monitored by in situ video. The advantage of this setup is that it requires a small quantity of these products to study the influence of the physicochemical parameters on crystallization. Crystallization mechanisms and kinetics are different depending on the starting position in the phase diagram and on the temperature reduction, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 20 publications
4
97
0
Order By: Relevance
“…The nucleation is clearly hampered by the LLPS. This is in agreement with previous results [5,16,40,41]. It is reported that in LLPS solution nucleation can take place in both the dispersed phase and the continuous phase [42] or at the interface between them [43].…”
Section: Time For Nucleation Of Llps Solutionsupporting
confidence: 93%
See 2 more Smart Citations
“…The nucleation is clearly hampered by the LLPS. This is in agreement with previous results [5,16,40,41]. It is reported that in LLPS solution nucleation can take place in both the dispersed phase and the continuous phase [42] or at the interface between them [43].…”
Section: Time For Nucleation Of Llps Solutionsupporting
confidence: 93%
“…Time for nucleation with 95% confidence interval and relative distance to the saturation of droplets solutions (Sols. [1][2][3][4][5][6][7][8][9][10][11][12] with 90-35% ethanol in solvents. Solid dots: average nucleation time of droplet solutions with 95% confidence interval.…”
Section: Time For Nucleation Of Llps Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel methods such as crystallization robots for high-throughput screening [1] and emulsion-based methods have been developed. Examples of the latter include spherical crystallization by the quasi-emulsion method [2,3], methods using the miscibility gap in the phase diagram [4] or microfluidic methods [5]. Working with small volume systems has already proved valuable and holds great promise for the control and the study of crystallization processes, for instance, producing crystals of controlled size [6].…”
Section: Introductionmentioning
confidence: 99%
“…This liquid-liquid demixing may hinder primary and secondary nucleation mechanisms. The occurrence of primary nucleation in the droplets at high supersaturation level was visualized [8]. The crystallization of fats and lipid systems in an oilin-water (O/W) emulsion is frequently encountered in the field of food science.…”
Section: Introductionmentioning
confidence: 99%